Agile-Driven Digital Transformation in Traditional Educational Institutions: Integrating Scrum, Automated Testing, and TAM for Student Registration Systems - Anis Nur Choiriyah; Nurcahya Pradana Taufik Prakisya; Rosihan Ari Yuana (Journal of Informatics and Vocational Education, 2025)
Agile methodologies' integration with automated testing and user acceptance evaluation within traditional Islamic boarding school (pesantren) contexts remains understudied. This study develops 'SIAP AMWIN', a web-based student registration system integrating Scrum, Katalon Studio automated testing, and TAM. R&D design was employed across five Scrum cycles (Aug 2023–Feb 2024). A validated 16-item TAM questionnaire (4 Usefulness + 12 Ease of Use items, expert-validated by 2 validators) was administered to 25 new students following system use. Blackbox testing was conducted via Katalon Studio. The system achieved Usefulness 13.96 and Ease of Use 41.44 (overall 86.56%, Very Good), a significant improvement over the prior system score of 12.1 (Not Good). Scrum-driven, actor-centered development effectively enables digital transformation in resource-constrained traditional institutions, providing a replicable blueprint for similar pesantren contexts.